GAMBARAN RADIOGRAFI PANORAMIK PASKA ODONTEKTOMI KONDISI ABNORMAL - Agung Pratama Akbar; Bayu Indra Sukmana; Sherli Diana (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground: The impacted tooth interferes with chewing function and causes various complications. The treatment performed by dentists for impacted teeth was odontectomy. Complications the odontectomy after odontectomy ranged from 2.6% - 30.9%. Purpose: This paper aims to obtain panoramic radiograph images after odontectomy with abnormal conditions. Methods: Articles were obtained from the search engines Pubmed, Semantic Scholar, and Google Scholar within the last five years of publication. Results: A total of 30 articles were obtained, found in 10 that Articles are fit the inclusion criteria, in English and Indonesian, in full paper form, and discussed post odontectomy panoramic photos with abnormal conditions. Discussion: The search for research articles on panoramic radiographs after odontectomy showed in 10 that Articles 3 abnormal conditions occurred after odontectomy. Conclusion: There are Lingual Nerve Injury, Inferior Alveolar Nerve, and Mandibular Angle Fracture, namely three abnormal conditions that happened after odontectomy, and there is the picture that abnormal after odontectomy based on age, sex, impact classification, odontectomy technique, and type of complication. Keywords: Abnormal odontectomy, Abnormal picture after odontectomy, panoramic radiography. ABSTRAKLatar Belakang Gigi impaksi mengganggu fungsi mengunyah dan menyebabkan berbagai komplikasi. Perawatan yang dilakukan oleh dokter gigi untuk gigi impaksi adalah odontektomi. Komplikasi odontektomi setelah odontektomi berkisar antara 2,6% - 30,9%. Tujuan: Makalah ini bertujuan untuk mendapatkan citra radiograf panoramik setelah odontektomi dengan kondisi tidak normal. Metode: Artikel diperoleh dari mesin pencari Pubmed, Semantic Scholar, dan Google Scholar dalam lima tahun terakhir publikasi. Hasil: Diperoleh total 30 artikel, ditemukan 10 artikel yang memenuhi kriteria inklusi, berbahasa Inggris dan Indonesia, dalam bentuk full paper, dan membahas foto panorama pasca odontektomi dengan kondisi abnormal. Diskusi: Pencarian artikel penelitian tentang radiografi panoramik setelah odontektomi menunjukkan pada 10 artikel bahwa kondisi abnormal terjadi setelah odontektomi. Kesimpulan: Terdapat Cedera Saraf Lingual, Saraf Alveolar Inferior, dan Fraktur Sudut Mandibula, yaitu tiga kondisi abnormal yang terjadi setelah odontektomi, dan ada gambaran yang abnormal setelah odontektomi berdasarkan usia, jenis kelamin, klasifikasi benturan, teknik odontektomi, dan jenis penyakit. komplikasi.Kata Kunci: Gambaran abnormal paska odontektomi, Odontektomi abnormal, Radiografi panoramic.